Evaluation of biochemical and clinical effects of hyaluronic acid on non-surgical periodontal treatment: a randomized controlled trial - Aydinyurt, Hacer Sahin; Akbal, Damla; Altindal, Dicle; Bozoglan, Alihan; Ertugrul, Abdullah Seckin; Demir, Halit (Springer London Ltd, 2020)
Background Recent studies reported that hyaluronic acid (HA) has anti-inflammatory, anti-edematous, and anti-bacterial activities in dentistry, particularly in gingival disorders caused by subgingival plaque microorganisms. Aims This study aimed to evaluate the early term effects of HA as an adjunct to scaling and root planing (SRP) on clinical parameters, periodontal inflamed surface area (PISA), and adenosine deaminase (ADA), catalase (CAT), and glutathione (GSH) levels in gingival crevicular fluid (GCF) in periodontitis. Methods A total of 24 periodontitis patients per group were included in this randomized-controlled study. The study population was divided into four groups: in Group 1: SRP+ saline; in Group 2: SRP + HA gel; in Group 3: SRP+ HA mouth rinse; and in Group 4: SRP + HA mouth rinse + HA gingival gel were applied. At baseline and week 4, clinical parameters and PISA were calculated. Also, biochemicals' (ADA, CAT, and GSH) levels were determined by spectrophotometric analysis. Results There was a statistically significant improvement in clinical parameters and PISA in all four groups in control sessions (p < 0.05). There was a significant decrease in ADA in GCF and significant increases in CAT and GSH levels after SRP (p < 0.05) in all four groups. The groups that were administered only gel (2nd and 4th) were different from other groups in terms of ADA, CAT, and GSH levels at 1st week (p < 0.05). Conclusion HA application as an adjunct to SRP did not affect the clinical results, although, in the control sessions following the application, the results were favorable for the biochemical data in gel-applied groups.
Keywords: Hyaluronic acid; Periodontics; Periodontitis; Periodontal treatment